Optimization of magneto-rheological fluid in squeeze mode using combined d-optimal mixture design - Siti Aishah, Wahid (2019)
Magneto-rheological (MR) fluids in squeeze mode able to produce stress resistance up to 80kPa which is exceeded most basic requirement of normal mechanical application. However, to attain the good performance of stress resistance at acceptable suspension stability, the composition of MR fluids has to be optimized. The aim of this study is to optimize the MR fluid materials’ component mixture in squeeze mode application through investigation on the effect of materials parameter on suspension stability and stress resistance. This study has been conducted through design of experiment (DOE) methodology using combined D-Optimal Mixture Design (CDMD) model. The CDMD allowed optimization of combined MR fluid components mixture and carrier fluid viscosity to produce relationship between material parameters and both stability and stress resistance. Ranges of materials composition were determined using factorial DOE and data from previous work. The investigated range of mineral oil (MO), carbonyl iron particles (CIP) and fumed silica (FS) were between 60-75vol%, 20-40vol% and 5- 10vol% respectively. Meanwhile the investigated range of carrier fluid viscosity was set between 18.5cP to 98.1cP. The stability was measured using sedimentation observation analysis while the stress resistances were measured using rheological analysis and compression test analysis. The finding of this study shows that increment of carrier fluid viscosity reduced sedimentation rate from 8.75% to 2.5% and reduced the compression stress resistance from 0.86MPa to 0.72MPa. Composition of CIP is the most significant factor to affect both sedimentation and stress resistance. Increment of CIP composition reduced the sedimentation rate but increased the stress resistance. Though FS composition shows least significant in the changes of stress resistance, it’s important to stabilize the suspension. Optimization of materials parameter through CDMD model analysis resulting five resultant compositions at desirability value of 1. The best resultant composition produced 0.09% of sedimentation rate, 89kPa of shear stress and 18.9MPa compression stress. This study shows stabilized MR fluid can be produced for squeeze mode application by selecting higher viscosity of carrier fluid and increasing magnetic particles composition. Optimization model produced in this study is crucial for composing dedicated MR fluid for squeeze mode MR devices.